Len Lye : a biography - Horrocks, Roger (Auckland University Press, 2013)
Len Lye: A Biography tells for the first time the story of an extraordinary New Zealander? a brilliant artist with an international career who never lost the informality, the energy and the independence of spirit of his South Pacific origins. Lye (1901?80) was a charismatic artist of enormous talent who became a leading figure in international modernism. He was a gifted innovator in many areas of the arts? film, painting, sculpture, photography and writing. Horrocks' exhaustive study of Lye is the result of twenty years of research and is based on interviews with many of those close to.